ANALISIS KIMIA KONSENTRAT IKAN GABUS (Ophiocepahlus striatus) DALAM KAPSUL PADA BEBERAPA KONDISI PENYIMPANAN - Julyaningsih, A. Hermina; Bakar Tawali, Abu; Mansyur Hamdani, Ibnu (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Fish protein concentrate is one of the methods used in the preparation of fish for human consumption, where protein is the main and most important element. Snakehead fish has a high protein content, specifically albumin protein, which is beneficial for the human body, especially in the wound healing process. The albumin protein concentrate in snakehead fish contains high levels of soluble protein (albumin) with the lowest fat content. Treatment using 0.1 M HCl solvent with heating at temperatures of 50-60°C resulted in an albumin content of 20.80% and a fat content of 1.78%. Albumin is soluble in water, so environmental conditions, particularly temperature, will affect the albumin content in snakehead fish concentrate capsules. In addition, the naturally occurring unsaturated fat content in snakehead fish meat undergoes chemical structural changes under various temperature conditions during storage. Therefore, this research was conducted to analyze the effect of temperature changes during storage on the chemical quality of the snakehead fish concentrate in capsules, including water content, ash content, albumin content, and TBA (thiobarbituric acid) value. The results of the study showed no significant changes in ash content, water content, and albumin content during storage at 28°C, 43°C, or 53°C. However, the TBA value increased, reaching its peak in the second week of storage at 28°C, the third week at 43°C, and the sixth week at 53°C. This indicates that the duration and storage temperature can affect the chemical quality of the snakehead fish concentrate in capsules.